2010
DOI: 10.1074/jbc.m110.144022
|View full text |Cite
|
Sign up to set email alerts
|

D1 and D2 Dopamine Receptor-mediated Inhibition of Activated Normal T Cell Proliferation Is Lost in Jurkat T Leukemic Cells

Abstract: Dopamine (DA)3 is one of the major neurotransmitters in the brain. In the central nervous system, it regulates various important functions like emotions, motivations, feelings of pleasure, addiction, and movement (1, 2). In the periphery, it regulates blood pressure, heart rate, gut motility, endocrine, and kidney functions (3-5). Recent reports indicate that DA influences different functions of the immune effector cells, most importantly normal T lymphocytes (6 -11). T lymphocytes can synthesize, transport, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
(49 reference statements)
2
36
0
Order By: Relevance
“…Stimulation of the dopamine D2 and D3 receptors will induce T-cell activation [36] whereas stimulation of the dopamine D1 and D2 receptors will inhibit the proliferation of activated T-cells and thus the release of cytokines [37]. The stimulation of the dopamine D4 receptors would induce T-cell quiescence [38].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the dopamine D2 and D3 receptors will induce T-cell activation [36] whereas stimulation of the dopamine D1 and D2 receptors will inhibit the proliferation of activated T-cells and thus the release of cytokines [37]. The stimulation of the dopamine D4 receptors would induce T-cell quiescence [38].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine also differentially modulates T cell functions in the pathological conditions like malignancies and autoimmune diseases (Basu and Dasgupta 2000b;Pacheco et al 2014). In malignancies, increased dopamine level inhibits proliferation and cytotoxicity of CD4+ and CD8+ T cells and this might suppress anti-neoplasmic immune response (Saha et al 2001;Basu et al 2010). However, decreased levels of dopamine found in autoimmune conditions could be responsible for an exacerbated response of autoreactive T cells (Giorelli et al 2005;Levite 2015).…”
Section: T Cells As a Mediator Of Neuro-immune Interactions: Dopaminementioning
confidence: 99%
“…5-HTR3, 5-HTR4, and 5-HTR7 receptors are now thought to be related to 5-HT induced Th2-cell differentiation of dendritic cells (DCs) [11]. Recent studies have revealed that T-cell activation can be induced by stimulating dopamine D2 and D3 receptors [12]. Other research results have indicated that stimulation of D1 and D2 receptors of T-cells will inhibit T-cells' activation and cytokine release [12].…”
Section: Introductionmentioning
confidence: 97%